Bilateral vocal cord palsy post thyroidectomy: lessons learnt. (24th March 2014) - Misron, Khairunnisak; Balasubramanian, Anusha; Mohamad, Irfan; Nik Hassan, Nik Fariza Husna
Abstract : Bilateral vocal cord paralysis is a known possible complication following thyroid surgery. It owes to the close relationship between the recurrent laryngeal nerve and the thyroid gland. The most feared complication of bilateral vocal cord paralysis is airway compromise. We report the case of a 39-year-old woman who underwent total thyroidectomy for multinodular goitre. The surgery was uneventful. However she developed stridor in the recovery bay needing intubation. We postulate that the cause was attributed to bilateral vocal cord paresis due to the use of the intraoperative nerve monitoring (IONM) whose high setting throughout the surgery was overlooked. She made a complete recovery without the need of a tracheostomy. We share our lessons learnt from this case.